Analisis Pola Interaksi Guru Dan Siswa Tunarungu Dalam Pembelajaran Di SLB Negeri Keleyan Bangkalan - Faris Fansuri Dwi Santoso; Nova Estu Harsiwi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The aim of this research is to find out: (1) How interaction patterns between teachers and deaf students are studied at the Keleyan Bangkalan State Special School; and (2) What factors hinder interaction between teachers and deaf students in learning at the Keleyan Bangkalan State Special School. This qualitative descriptive research interviewed one teacher. Data was collected through observation, interviews and documentation. Data analysis and drawing conclusions are data collection techniques. (1) The interaction patterns of teachers and deaf students in learning are shown by the research results: a) the use of verbal patterns, which is carried out by combining verbal and non-verbal communication, so that deaf students can get used to using verbal patterns; b) the use of nonverbal patterns in learning interactions between teachers and students by teaching the alphabet word by word, so that students can understand the material provided. (2) Factors that hinder teacher interaction are a) psychological factors of deaf students because they have low intelligence, which makes it difficult for them to understand the material, and b) semantic factors because deaf students have to repeat lesson material. In addition, teachers try to interpret one word at a time during learning interactions because deaf students have difficulty in semantics.